STING-mediated neuroinflammation: a therapeutic target in neurodegenerative diseases - Zhang, Haoqin; He, Ziyang; Yin, Can; Yang, Shiyi; Li, Jianqiao; Lin, Hong; Hu, Guishan; Wu, Anguo; Qin, Dalian; Hu, Guangqiang; Yu, Lu (Frontiers in Aging Neuroscience, 2025)
The stimulator of interferon genes (STING) plays a crucial role as an adaptor in innate immune defense, orchestrating key inflammatory processes through the modulation of type I interferon signaling and activation of cytokine networks. Recent studies have identified STING-induced neuroinflammatory responses as a major factor in the progression of neurological diseases, particularly in neurodegenerative disorders. This review methodically explores the structural basis of STING activation and its role in driving pathological inflammation. And the classic and non-classic pathways of STING as well as their roles in neurodegenerative diseases were discussed. Additionally, it critically assesses new pharmacological approaches that target the STING pathway, emphasizing anti-inflammatory treatments ranging from synthetic small-molecule inhibitors to bioactive compounds sourced from traditional Chinese medicines, which aim to mitigate neurotoxic inflammation. By combining mechanistic insights with therapeutic advancements, this paper presents an innovative transformation framework aimed at developing anti-inflammatory therapies targeting the STING pathway to treat neurodegenerative diseases. The core contribution of this framework lies in systematically bridging the innate immune regulation and neuroinflammation control mechanisms, providing a new strategy for disease intervention.